Dermatitis neglecta of the vulva - Aoife Granahan; Huda Fadlelseed; Niamh Nolan; Donal O'Brien; Aoife Lally (Wiley, 2023)
Abstract Dermatitis neglecta (DN) is a condition that arises secondary to inadequate cleansing and self‐neglect leading to the accumulation of epidermal debris, corneocytes and sebum. Rarely reported, it is often diagnostically challenging and can mimic other pathologies. It typically arises in cases of chronic disability or psychiatric illness. We present the case of a 72‐year‐old lady with extensive hyperkeratotic plaques of the vulva. Initial clinical impression was that of a malignant or infectious process and skin biopsies were performed. However, with intensive topical care and education, complete resolution was achieved. Frequent relapses of vulval DN occurred over the subsequent months, where secondary gain was identified with increased care and attention from family and friends.